Symbolism in Hindu Worship - Malieckal, Louis (Journal of Dharma, 1984)
This article is not a survey of the many kinds of images and symbols that could be found in the entire spectrum of Hindu worship. Certainly the question of ’Svmbolism in Hindu Worship’ can be approached this way, and then it would call for a different method and a more elaborate discussion. The aim of the present study is rather to establish the rationale behind the development of the main symbolic forms in worship, although some models of these forms will also have to be considered in order to illustrate the main point mentioned. We shall divide this study in three parts : a general discussion of the symbolic nature of man as homo religiosus and of the Hindu cultic activity (part I); an enquiry about the basic orientations of the Indian world-vision (part Il); and an investigation of the dynamics of the Hindu worship-symbolism arising out of this peculiar world-visoin (part 111)